ASSESMENT OF THE MORPHOLOGY OF THE PANCREAS IN DIABETIC COMPLICATIONS (Conferencea, 2023)
Study of the effect of the new drug "Rheomannisol" on vital organs, taking into account pathomorphological aspects in the complex treatment of experimental diabetic foot syndrome.